The Use of Media Educational Technologies in Formation of Multicultural Competence of Future Translators: Ukrainian Experience - Bakhov, Ivan Stepanovich; Motsar, Mariia Nikolaevna (International Review of Management and Marketing, 2015)
The article considers study of characteristics of the introduction of media education technologies in forming multicultural competence of translators in higher educational institutions. It considers features and advantages of distance learning of today, gives the analysis of approaches to the use of Internet technologies in the educational process of training future translators. It emphasizes the role of multicultural education in the formation of professional qualities of translators, which resulted in increased persistence, academic achievement, civic responsibility, in the development of human relationships, personal development and the development of social belonging, and successful maneuver in the professional sphere. Distance learning and the process of formation of translators' multicultural competence is presented as a process of familiarizing students with the values of social consciousness, which is the basic mechanism of the information learning environment based on media technologies, with access to the global Internet, as well as using country study analysis. Keywords: multiculturalism, professional training, translator, media technologies, multicultural competence, distance learning, cultural diversity. JEL Classificatios: O35, Z11, Z19, Z18